2002
DOI: 10.1093/emboj/21.9.2231
|View full text |Cite
|
Sign up to set email alerts
|

WSTF-ISWI chromatin remodeling complex targets heterochromatic replication foci

Abstract: The Williams Syndrome Transcription Factor (WSTF), the product of the WBSCR9 gene, is invariably deleted in the haploinsufficiency Williams–Beuren Syndrome. Along with the nucleosome‐dependent ATPase ISWI, WSTF forms a novel chromatin remodeling complex, WICH (WSTF–ISWI chromatin remodeling complex), which is conserved in vertebrates. The WICH complex was purified to homogeneity from Xenopus egg extract and was found to contain only WSTF and ISWI. In mouse cells, WSTF interacts with the SNF2H isoform of ISWI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
195
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(209 citation statements)
references
References 52 publications
(117 reference statements)
11
195
0
3
Order By: Relevance
“…We and others have found that Snf2h protein is detectable in ES cells (Fig. 1C) (16). This finding suggests that Snf2h also plays an essential role at a very early stage in development, a role that is not revealed in Snf2h-null embryos because of the maternal contribution.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We and others have found that Snf2h protein is detectable in ES cells (Fig. 1C) (16). This finding suggests that Snf2h also plays an essential role at a very early stage in development, a role that is not revealed in Snf2h-null embryos because of the maternal contribution.…”
Section: Discussionsupporting
confidence: 51%
“…For example, the NORC complex, containing the ISWI ATPase Snf2h and nucleolar protein Tip5, has been shown to repress ribosomal gene transcription by recruiting DNA methyltransferase and histone deacetylase activities to rDNA promoters (13,14). Snf2h also localizes in heterochromatin through its interactions with Acf1 (15) and the Williams Syndrome transcription factor (16). These complexes accumulate at sites in heterochromatin coincident with their replication, suggesting a role for ISWI chromatin remodeling functions in replication of DNA in highly condensed chromatin (15).…”
mentioning
confidence: 99%
“…The Drosophila ISWI protein is a common subunit of the NURF, CHRAC and ACF complexes. In vertebrates, members of the ISWI subfamily are the ATPase subunits of the RSF complex, (23) hACF/WCRF complex, (29,45) xACF, (46) WICH complex, (47) hCHRAC (48) and NoRC. (49) In addition, ISW1 and ISW2 are the catalytic subunits of chromatin-remodeling complexes in yeast.…”
Section: Activities Of Chromatin-remodeling Factorsmentioning
confidence: 99%
“…The in vitro activities of the WSTF-ISWI complex are essentially identical to ACF. WSTF-ISWI is targeted to pericentric heterochromatin during replication and is believed to allow heterochromatin reassembly in the wake of the replication fork (Bozhenok et al 2002). It is tempting to speculate that ACF and CHRAC may have similar functions in Drosophila and could be implicated in the establishment of repressive chromatin structures after replication.…”
Section: Physiological Activities Of the Iswi Chromatin Remodeling Mamentioning
confidence: 99%